Profit Maximization and the Market Selection Hypothesis - Dutta, Prajit K.; Radner, Roy (Review of Economic Studies, 1999)
We examine the proposition that competitive firms must behave as if they were maximizing profits; otherwise they would go bankrupt, or even fail to be financed in a competitive capital market. We investigate a model in which an entrepreneur raises funds for a risky enterprise on a competitive capital market, by offering a “dividend policy” based on the realized (stochastic) flow of earnings. We show that an entrepreneur who maximizes the expected sum of discounted dividends is sure to fail in finite time. On the other hand, many other behaviours yield positive expected profits and are able to attract investment funds, and yet result in a positive probability of surviving forever. As a consequence, if new firms have sufficiently diverse behaviours, then even if there is a constant stream of new entrants, after a long time practically all of the surviving firms will not have been maximizing profits.